Identification of Toscana virus in natural population of sand flies (Diptera: Psychodidae) from Moroccan leishmaniasis foci. Issue 4 (April 2022) - Daoudi, Mohamed; Calzolari, Mattia; Boussaa, Samia; Bonilauri, Paolo; Torri, Deborah; Romeo, Giuseppe; Lelli, Davide; Lavazza, Antonio; Hafidi, Mohamed; Dottori, Michele; Boumezzough, Ali
Abstract: Background: Phlebotomine sand flies are known as vectors of various pathogens such as Leishmania sp parasite and Toscana virus (TOSV). Leishmaniasis is endemic in Morocco, and TOSV is increasingly reported. Our objective is to analyze the specific composition of the natural population of sand flies in endemic and non endemic area of leishmaniasis in Morocco, thus evaluated their infection by Toscana virus. Methods: Sand flies were collected by CDC miniature light traps from seven different localities with an altitude range from 399 m to 1496 m. Synanthropic index was calculated for each sand fly species. The collected female sand flies were grouped in 73 pools, with a maximum of 50 specimens per pool, and submitted to real time PCR for TOSV detection. Results: 8 sand fly species were identified morphologically: 5 of the Phlebotomus genus and 3 of the Sergentomyia genus. Phlebotomus sergenti was the most abundant species comprising of 43, 12% of identified sand flies, followed by P. papatasi (18, 89%) and P. longicuspis (13, 43%). Estimated synanthropic indices for these species were between + 1.1 and + 12.6 suggesting a high preference to anthropogenic environments. A total of 3558 sand fly females were grouped in 73 pools (up to 50 sand flies per pool) for TOSV detection. TOSV was detected in one pool (out of 6 tested) from Lalla Laaziza locality (Chichaoua Province) where P. sergenti was the most abundant sand fly species. Conclusion: We reported the TOSV for the first time in a central Morocco, where cutaneous leishmaniasis by L. tropica is endemic. This result has epidemiological importance for both researchers and health authorities to monitor circulation of TOSV and implement a surveillance plan of sand fly-borne phleboviruses in Morocco. Highlights: Toscana virus is circulating in Morocco. Toscana virus was detected in field-collected sand flies from an active Moroccan focus of cutaneous leishmaniasis. In the site tested positive for Toscana virus the most abundant species is Phlebotomus sergenti .